2008
DOI: 10.1007/s12206-008-0407-8
|View full text |Cite
|
Sign up to set email alerts
|

Wear behavior of diamond wheel for grinding optical connector ferrule — FEA and wear test —

Abstract: The grinding characteristics and the wear behavior of diamond wheel for grinding the optical connector ferrule were investigated by finite element analysis (FEA) and wear test. FEA of contact between diamond wheel and ferrule shows that the subsurface damage area of ferrule is 13µm from the interface of abrasive particle and matrix. Fallout of abrasive particle is affected by the stress state at the interface. A 2-D finite element model was established to calculate the distribution of stress at the interface. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…To understand the grain-matrix bonding failure, Zhou et al [26] used a two-dimensional finite element model to compare the stresses at the grain-matrix interface. Suh et al [27] analyzed the stress distributions in grains in resin-bonded diamond wheels during the grinding of an optical connector ferrule, and reported that the grain breaking could be quantified by the ratio of critical protrusion height to grain diameter. Geometry effect of grains has also been studied, such as spherical [24,25] and pyramidal [26,27] grains.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To understand the grain-matrix bonding failure, Zhou et al [26] used a two-dimensional finite element model to compare the stresses at the grain-matrix interface. Suh et al [27] analyzed the stress distributions in grains in resin-bonded diamond wheels during the grinding of an optical connector ferrule, and reported that the grain breaking could be quantified by the ratio of critical protrusion height to grain diameter. Geometry effect of grains has also been studied, such as spherical [24,25] and pyramidal [26,27] grains.…”
Section: Introductionmentioning
confidence: 99%
“…Suh et al [27] analyzed the stress distributions in grains in resin-bonded diamond wheels during the grinding of an optical connector ferrule, and reported that the grain breaking could be quantified by the ratio of critical protrusion height to grain diameter. Geometry effect of grains has also been studied, such as spherical [24,25] and pyramidal [26,27] grains. In the studies by Zhou et al [26] and Suh et al [27], however, the depth of a grain embedded in a bonding layer was beyond 60% of the grain diameter, indicating that the grain protrusion, or the exposing height of the grain above the bonding layer was low.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hard-brittle materials are featured by high level of hardness, thermal stability, and corrosion resistance, thus enjoying a wide range of application in national defense, aerospace industry, precision instrument, and so on. [1][2][3] Quick-point grinding combines high surface quality of grinding and high efficiency of turning, and so far it has been widely utilized in the processing of axles. 4 Among others, YD Gong et al 5 conducted research in the parameter relationship between temperature field and surface micro hardness in quickpoint grinding.…”
Section: Introductionmentioning
confidence: 99%
“…The column can be driven around (X axis) through the screw rod of the base. Finite element method is widely used in structural design of machining center and got a good validation [5][6][7]. In this paper, the stress and deformation distributions under different conditions are simulated by ABAQUS software.…”
Section: Introductionmentioning
confidence: 99%